Pelatihan Penerapan CPPOB sebagai Upaya Peningkatan Kualitas Gula Aren Cair pada Kelompok Tani Hutan Giri Madia - Fuadi, Mi’raj; AP, Yuhendra; Rini Nofrida; Raphael Bianco Huwae; Lalu Muhammad Furkan; Kurniawan Yuniarto; Fitria Dea Ananda; M. Rizki Alfariji; Muhamad Munzir (Universitas Mataram, 2025)
Palm sugar (Arenga pinnata Merr.) is a traditional sweetener that has been produced by Indonesian people for a long time and plays an important role in the rural economy. However, the quality of liquid palm sugar is greatly influenced by the easily fermented nature of the sap and the uneven production practices. This community service activity aims to improve the quality and safety of liquid palm sugar through training on Good Manufacturing Practices equipment at the Giri Madia Forest Farmers Group (KTH). The training was held on August 21, 2025, in Giri Madia Village, Lingsar District, West Lombok, with 20 participants. The method included interactive lectures, demonstrations, and hands-on practice focusing on the prerequisites for CPPOB and controlling the liquid palm sugar process using affordable equipment (food-grade containers, stainless steel sieves, thermometers, pH meters, and refractometers for °Brix control). The results of the activity showed a significant increase in participants' understanding of identifying critical control points and implementing proper sanitation procedures. It is hoped that consistent implementation of CPPOB will not only guarantee product quality and safety, but also strengthen the competitiveness of liquid palm sugar in the wider market, while encouraging the strengthening of the local potential-based economy.